Adaptation to an Unfamiliar Accent by Child L2 Listeners. (September 2021) - Hu, Chieh-Fang
The study examines school-aged L2 listeners' adaptation to an unfamiliar L2 accent and learner variables predicting such adaptation. Fourth-grade Mandarin L1 learners of English as a foreign language ( N = 117) listened to a story twice in one of three accent conditions. In the single-talker condition, the story was produced by an Indian English (IE) speaker. In the multi-talker condition, the story was produced by two IE speakers. In the control condition, the story was produced by a Mandarin-accented speaker. Children's (re)interpretation of IE words/nonwords was assessed by referent selection tests administered before and after the first and the second exposures to the story. Repeated exposure to IE-accented speech forms influenced performance: the participants demonstrated better recognition of IE words across the referent selection tests but worse (re)interpretation of IE nonwords sounding similar to existing lexical items. Exposure to an IE-accented story yielded an additional advantage in word recognition, but the advantage was limited to words heard in the story. Furthermore, children's English phonological awareness, phonological memory, and vocabulary predicted their reinterpretation performance of the accented forms. These results suggest that school-aged L2 listeners with better phono-lexical representations develop better capacity in adapting to an unfamiliar accent of a foreign language by loosening their acceptability criteria for word recognition but the adaptation does not necessarily entail perceptual tuning to the specific phonological categories of the accent.